Electrophotographic charging rolls

The charging roll design with spirally formed grooves and controlled particle placement on the elastic layer addresses the issue of particle aggregation, ensuring uniform discharge characteristics and reducing image defects.

JP7621041B2Active Publication Date: 2025-01-24SUMITOMO RIKO CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021025091
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-19
Publication Date
2025-01-24
Estimated Expiration
2041-02-19

AI Technical Summary

Technical Problem

The uniformity of surface roughness and discharge characteristics in charging rolls for electrophotographic equipment deteriorates due to aggregation of roughness-forming particles with different sizes, particularly affecting the uniformity of discharge characteristics.

Method used

A charging roll design featuring a shaft with an elastic layer and a surface layer, where grooves spirally formed along the axial direction on the elastic layer have specific dimensions, and roughness-forming particles are arranged on both flat and groove parts with varying thicknesses of binder polymer coverage to maintain uniformity.

Benefits of technology

The design enhances the uniformity of discharge characteristics by controlling particle aggregation and adjusting the thickness of the binder polymer, reducing chargeability variations and improving discharge consistency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621041000003
    Figure 0007621041000003
  • Figure 0007621041000004
    Figure 0007621041000004
  • Figure 0007621041000005
    Figure 0007621041000005
Patent Text Reader

Abstract

To provide a charging roll for an electro-photographic apparatus excellent in uniformity of discharge characteristics.SOLUTION: In a charging roll 10, a groove part 22 is formed with a regular spiral shape along an axial direction of an outer peripheral surface of an elastic body layer 14, with a groove width w of 4 to 280 μm and a groove depth d of 2 to 30 μm. In an outer peripheral surface of the elastic body layer 14, an area ratio a / b is 0.3 to 2.4 with regard to an area a of a bottom face 221 of the groove part 22 and an area b of a plane part 24. A surface layer 16 includes a binder polymer 16a and roughness formation particles 18. The roughness formation particles 18 are respectively arranged on the plane part 24 and the groove part 22. Surface roughness Rz is 5 to 26 μm with regard to the surface layer 16 at a region M on the groove part 22. Surface roughness Rz is 2 to 16 μm with regard to an entirety of the surface layer 16. Thickness t1 of the binder polymer 16a covering roughness formation particles 18a on the groove part 22 is thicker than thickness t2 of the binder polymer 16a covering roughness formation particles 18b on the plane part 24.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a charging roll for electrophotographic equipment, which is suitably used in electrophotographic equipment such as copying machines, printers, and facsimiles that employ an electrophotographic system. [Background technology]

[0002] Known electrostatic charge rolls for electrophotographic devices include those having an elastic layer having rubber elasticity on the outer circumferential surface of a shaft such as a core metal, and having a surface layer on the outer circumferential surface of the elastic layer. In addition, in electrostatic charge rolls, for example, for charging characteristics, roughness-forming particles may be added to the binder polymer of the surface layer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication 2018 / 025870 Summary of the Invention [Problem to be solved by the invention]

[0004] However, since the roughness-forming particles added to the surface layer are prone to aggregation, the uniformity of the surface roughness is likely to decrease in the roughness-forming method in which the roughness-forming particles are added. In particular, when attempting to form surface irregularities using two or more types of roughness-forming particles with different particle sizes, the particles with different particle sizes aggregate, so the uniformity of the surface roughness is particularly likely to decrease. If the uniformity of the surface roughness decreases, there is a risk that the uniformity of the discharge characteristics of the charging roll will decrease.

[0005] An object of the present invention is to provide a charging roll for electrophotographic equipment which has excellent uniformity in discharge characteristics. [Means for solving the problem]

[0006] The electrostatic charging roll for an electrophotographic device according to the present invention comprises a shaft, an elastic layer formed on the outer peripheral surface of the shaft, and a surface layer formed on the outer peripheral surface of the elastic layer, wherein grooves are formed on the outer peripheral surface of the elastic layer so as to regularly spiral along the axial direction, the grooves have a groove width of 4 μm or more and 280 μm or less, and a groove depth of 2 μm or more and 30 μm or less, and the area ratio a / b of the area a of the bottoms of the grooves to the area b of the flat portions other than the grooves on the outer peripheral surface of the elastic layer is 0.3 or more and 2.4 or less. the surface layer contains a binder polymer and roughness-forming particles, the roughness-forming particles are respectively arranged on the flat portion and the groove portion of the elastic layer, the surface roughness Rz of the surface layer in the region above the groove portion is 2 μm or more and 16 μm or less, the surface roughness Rz of the entire surface layer is 5 μm or more and 26 μm or less, and the thickness of the binder polymer covering the roughness-forming particles on the groove portion is thicker than the thickness of the binder polymer covering the roughness-forming particles on the flat portion.

[0007] The roughness-forming particles may be composed of one type of particle. The material of the roughness-forming particles may be any one of polyurethane, polyamide, and acrylic resin. The average particle diameter of the roughness-forming particles may be 3 μm or more and 32 μm or less. The difference between the thickness of the binder polymer covering the roughness-forming particles on the flat portion and the thickness of the binder polymer covering the roughness-forming particles on the groove portion may be 4 μm or more and 16 μm or less. The elastic layer may include any one or more of isoprene rubber, nitrile rubber, and hydrin rubber. The binder polymer of the surface layer may be any one of polyurethane and polyamide. The outer peripheral surface of the elastic layer may be formed with a mesh-like groove portion in which a groove portion that regularly draws a right-handed spiral along the axial direction and a groove portion that regularly draws a left-handed spiral along the axial direction intersect. Effect of the Invention

[0008] The electrostatic charge roll for electrophotographic equipment according to the present invention comprises a shaft, an elastic layer formed on the outer peripheral surface of the shaft, and a surface layer formed on the outer peripheral surface of the elastic layer, and a groove portion that regularly spirals along the axial direction is formed on the outer peripheral surface of the elastic layer, the groove portion has a groove width of 4 μm or more and 280 μm or less, and a groove depth of the groove portion is 2 μm or more and 30 μm or less, and an area ratio a / b of an area a of a bottom surface of the groove portion to an area b of a flat portion that is a portion other than the groove portion on the outer peripheral surface of the elastic layer is 0.3 or more and 2.4 or less, The surface layer contains a binder polymer and roughness-forming particles, the roughness-forming particles being arranged on the flat portion and the groove portion of the elastic layer, respectively; the surface roughness Rz of the surface layer in the region above the groove portion is 2 μm or more and 16 μm or less, and the surface roughness Rz of the entire surface layer is 5 μm or more and 26 μm or less; and the thickness of the binder polymer covering the roughness-forming particles on the groove portion is thicker than the thickness of the binder polymer covering the roughness-forming particles on the flat portion, resulting in excellent uniformity in discharge characteristics.

[0009] When the roughness-forming particles are composed of one type of particles, the uneven shape of the elastic layer is easily reflected in the surface unevenness of the charging roll, making it easy to control the surface unevenness of the charging roll. In addition, the aggregation of the roughness-forming particles is easily controlled, making it possible to improve the uniformity of the surface roughness. Furthermore, the thickness of the binder polymer covering the roughness-forming particles is easily adjusted, making it possible to improve the uniformity of the discharge characteristics.

[0010] When the material of the roughness-forming particles is any one of polyurethane, polyamide, and acrylic resin, the roughness-forming particles are made of a material with a high dielectric constant, and thus the electrostatic chargeability of the roll surface is improved.

[0011] When the average particle diameter of the roughness-forming particles is 3 μm or more and 32 μm or less, appropriate unevenness is easily formed, which can improve the uniformity of the discharge characteristics.

[0012] When the difference between the thickness of the binder polymer covering the roughness-forming particles on the flat portion and the thickness of the binder polymer covering the roughness-forming particles on the groove portion is 4 μm or more, the amount of charge on the surface of the binder polymer covering the roughness-forming particles on the flat portion becomes relatively large, and the range of environments in which black spot images do not occur is expanded. Also, when the difference in thickness is 16 μm or less, the appropriate thickness is maintained, so that appropriate unevenness is easily formed. This can improve the uniformity of the discharge characteristics.

[0013] When the elastic layer contains at least one of isoprene rubber, nitrile rubber, and hydrin rubber, the compression set is small, and the occurrence of streak images corresponding to the deformed portions when the charging roll is set is suppressed.

[0014] When the binder polymer of the surface layer is one of polyurethane and polyamide, the binder polymer is made of a material with a high dielectric constant, which improves the chargeability of the roll surface. In addition, the compression set is small, and the occurrence of streak images corresponding to the deformation parts when the charging roll is set is suppressed.

[0015] When a mesh-like groove portion is formed on the outer peripheral surface of the elastic layer, in which groove portions that regularly spiral in a right-handed manner along the axial direction intersect with groove portions that regularly spiral in a left-handed manner along the axial direction, the uniformity of the surface roughness is improved, and the uniformity of the discharge characteristics can be improved. [Brief description of the drawings]

[0016] [Figure 1] 1A is a schematic external view of a charging roll for an electrophotographic device according to one embodiment of the present invention, and FIG. 1B is a cross-sectional view taken along line AA thereof. [Diagram 2] 4 is a schematic external view of an elastic layer, illustrating the shape of a groove formed in the outer peripheral surface of the elastic layer. FIG. [Diagram 3] FIG. [Figure 4] 10A to 10C are schematic external views of an elastic layer showing modified shapes of grooves formed in the outer peripheral surface of the elastic layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] A charging roll for electrophotographic equipment (hereinafter, sometimes simply referred to as a charging roll) according to the present invention will be described in detail. Fig. 1 is a schematic external view (a) of a charging roll for electrophotographic equipment according to one embodiment of the present invention, and its AA line cross-sectional view (b). Fig. 2 is a schematic external view of an elastic layer showing the shape of a groove portion formed on the outer peripheral surface of the elastic layer. Fig. 3 is an enlarged cross-sectional view of the surface layer.

[0018] The electrostatic charge roll 10 includes a shaft 12, an elastic layer 14 formed on the outer peripheral surface of the shaft 12, and a surface layer 16 formed on the outer peripheral surface of the elastic layer 14. The elastic layer 14 is a layer (base layer) that serves as the base of the electrostatic charge roll 10. The surface layer 16 is a layer that appears on the surface of the electrostatic charge roll 10. Although not particularly shown, an intermediate layer such as a resistance adjustment layer may be formed between the elastic layer 14 and the surface layer 16 as necessary.

[0019] The shaft body 12 is not particularly limited as long as it is conductive. Specific examples include a core bar made of a solid or hollow body made of a metal such as iron, stainless steel, or aluminum. An adhesive, primer, or the like may be applied to the surface of the shaft body 12 as needed. In other words, the elastic layer 14 may be bonded to the shaft body 12 via an adhesive layer (primer layer). The adhesive, primer, or the like may be made conductive as needed.

[0020] As shown in FIG. 2, the grooves 22 are formed on the outer peripheral surface of the elastic layer 14 in a regular spiral shape along the axial direction. More specifically, the grooves 22 are formed in a mesh shape in which the grooves 22a are formed in a regular right-handed spiral shape along the axial direction and the grooves 22b are formed in a regular left-handed spiral shape along the axial direction. Regular means that the grooves 22 are formed at regular intervals in the axial direction. The portion of the outer peripheral surface of the elastic layer 14 other than the grooves 22 is a flat portion 24. As shown in FIG. 3, the flat portion 24 protrudes radially outward from the bottom surface 221 of the groove 22. The elastic layer 14 has a surface unevenness formed on the outer peripheral surface by the bottom surface 221 of the groove 22 arranged relatively inward in the radial direction and the flat portion 24 arranged relatively outward in the radial direction. Since the grooves 22 are formed in a regular spiral shape along the axial direction, the outer peripheral surface of the elastic layer 14 has a uniform surface unevenness. In addition, a mesh-like groove portion 22 is formed in which groove portion 22a, which regularly spirals in a right-handed manner along the axial direction, and groove portion 22b, which spirals in a left-handed manner, intersect with each other, so that the outer peripheral surface of elastic layer 14 has a more uniform surface unevenness than one having a groove portion that is not mesh-like.

[0021] The groove width w of the groove portion 22 is 4 μm or more and 280 μm or less. The groove depth d of the groove portion 22 is 2 μm or more and 30 μm or less. In the outer peripheral surface of the elastic layer 14, the area ratio a / b of the area a of the bottom surface 221 of the groove portion 22 to the area b of the flat portion 24 is 0.3 or more and 2.4 or less.

[0022] If the groove width w of the groove portion 22 is less than 4 μm, the groove width w is too small and the roughness-forming particles 18 cannot enter the groove portion 22. As a result, the difference between the surface roughness Rz caused by the roughness-forming particles 18b on the flat portion 24 and the surface roughness Rz caused by the roughness-forming particles 18a on the groove portion 22 becomes small, and horizontal streaks occur due to insufficient charging. If the roughness-forming particles 18 that fit into the small groove width w are used, roughness that ensures sufficient discharge cannot be formed. From this point of view, the groove width w of the groove portion 22 is preferably 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, 40 μm or more, 50 μm or more, etc., according to the average particle diameter of the roughness-forming particles 18 used.

[0023] If the groove width w of the groove portion 22 exceeds 280 μm, the groove width w is too large, and the roughness-forming particles 18 cannot be uniformly arranged in the groove portion 22. If the roughness-forming particles 18 of a size that matches the large groove width w are used, the convex portion caused by the roughness-forming particles 18 becomes too large, the surface roughness becomes too large, and the surface roughness cannot be made appropriate. As a result, uniform discharge characteristics cannot be obtained. In addition, if the groove width w is too large, the binder polymer 16a covering the roughness-forming particles 18 on the groove portion 22 is likely to come into contact with the photoconductor, so that not only the binder polymer 16a covering the roughness-forming particles 18b on the flat portion 24 and the roughness-forming particles 18b thereunder are worn, but also the binder polymer 16a covering the roughness-forming particles 18a on the groove portion 22 and the roughness-forming particles 18a thereunder are worn, so that the entire surface of the surface layer 16 is worn during durability, causing unevenness in the image. From this viewpoint, the groove width w of the grooves 22 may be set to 250 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, depending on the average particle diameter of the roughness-imparting particles 18 used.

[0024] If the groove depth d of the groove portion 22 is less than 2 μm, the groove depth d is too small, and the difference between the surface roughness Rz caused by the roughness-forming particles 18b on the flat surface portion 24 and the surface roughness Rz caused by the roughness-forming particles 18a on the groove portion 22 becomes too small, resulting in horizontal streaks due to insufficient charging. If small roughness-forming particles 18 are used in accordance with a small groove depth d, roughness that ensures sufficient discharge cannot be formed. From this point of view, the groove depth d of the groove portion 22 is preferably 3 μm or more, 5 μm or more, 10 μm or more, etc., in accordance with the average particle diameter of the roughness-forming particles 18 used.

[0025] If the groove depth d of the groove portion 22 exceeds 30 μm, the groove depth d is too large, and the roughness-forming particles 18 arranged in the groove portion 22 cannot form surface roughness on the groove portion 22. For this reason, black spots (fog) occur on the image after durability testing. If large roughness-forming particles 18 are used in accordance with a large groove depth d, the difference between the surface roughness Rz caused by the roughness-forming particles 18b on the flat portion 24 and the surface roughness Rz caused by the roughness-forming particles 18a on the groove portion 22 becomes too large, making it difficult to discharge. From this point of view, the groove depth d of the groove portion 22 is preferably set to 25 μm or less, 20 μm or less, etc., in accordance with the average particle diameter of the roughness-forming particles 18 used.

[0026] If the area ratio a / b between the area a of the bottom surface 221 of the groove portion 22 and the area b of the flat portion 24 is less than 0.3 or exceeds 2.4, the balance between the area a of the bottom surface 221 and the area b of the flat portion 24 becomes poor, and the uniformity of the surface unevenness decreases. This makes it easy for uneven images to occur after durability testing. Furthermore, if the balance between the area a of the bottom surface 221 and the area b of the flat portion 24 becomes poor, the adhesion between the elastic layer 14 and the surface layer 16 decreases. From this perspective, the area ratio a / b is preferably 0.5 or more, 0.7 or more, etc., and is preferably 2.0 or less, 1.8 or less, 1.5 or less, etc.

[0027] The groove width w of the groove portion 22 is calculated from the average of the groove widths w of 100 points of the groove portion 22 observed in an image of the outer peripheral surface of the elastic layer 14 taken with a laser microscope. The groove depth d of the groove portion 22 is calculated from the average of the groove depths d of 100 points of the groove portion 22 observed in an image of the radial cross section of the elastic layer 14 taken with a laser microscope. The area ratio a / b of the area a of the bottom surface 221 of the groove portion 22 to the area b of the flat portion 24 is calculated from the average ratio of the area a of the bottom surface 221 of the groove portion 22 and the area b of the flat portion 24 observed in a predetermined range (0.1 mm x 0.1 mm) of the image taken with a laser microscope at any five points on the outer peripheral surface of the elastic layer 14.

[0028] The elastic layer 14 contains a crosslinked rubber. The elastic layer 14 is formed of a conductive rubber composition containing an uncrosslinked rubber. The crosslinked rubber is obtained by crosslinking the uncrosslinked rubber. The uncrosslinked rubber may be a polar rubber or a non-polar rubber.

[0029] The polar rubber is a rubber having a polar group, and examples of the polar group include a chloro group, a nitrile group, a carboxyl group, and an epoxy group. Specific examples of the polar rubber include hydrin rubber, nitrile rubber (NBR), urethane rubber (U), acrylic rubber (a copolymer of an acrylic acid ester and 2-chloroethyl vinyl ether, ACM), chloroprene rubber (CR), and epoxidized natural rubber (ENR). Among the polar rubbers, hydrin rubber and nitrile rubber (NBR) are more preferable from the viewpoint that the volume resistivity is particularly likely to be low.

[0030] Examples of the hydrin rubber include epichlorohydrin homopolymer (CO), epichlorohydrin-ethylene oxide binary copolymer (ECO), epichlorohydrin-allyl glycidyl ether binary copolymer (GCO), and epichlorohydrin-ethylene oxide-allyl glycidyl ether terpolymer (GECO).

[0031] The urethane rubber may be a polyether type urethane rubber having an ether bond in the molecule. The polyether type urethane rubber may be produced by reacting a polyether having hydroxyl groups at both ends with a diisocyanate. The polyether may be, but is not limited to, polyethylene glycol, polypropylene glycol, etc. The diisocyanate may be, but is not limited to, tolylene diisocyanate, diphenylmethane diisocyanate, etc.

[0032] Examples of non-polar rubbers include silicone rubber (Q), isoprene rubber (IR), natural rubber (NR), styrene butadiene rubber (SBR), butadiene rubber (BR), etc. Among non-polar rubbers, silicone rubber is more preferable from the viewpoints of low hardness and resistance to sagging (excellent elastic recovery).

[0033] The elastic layer 14 may contain at least one of isoprene rubber, nitrile rubber, and hydrin rubber. When the elastic layer 14 contains at least one of isoprene rubber, nitrile rubber, and hydrin rubber, the compression set is small, and the occurrence of streak images corresponding to the deformed parts when the charging roll 10 is set is suppressed.

[0034] Examples of the crosslinking agent include a sulfur crosslinking agent, a peroxide crosslinking agent, and a dechlorination crosslinking agent. These crosslinking agents may be used alone or in combination of two or more.

[0035] Examples of the sulfur crosslinking agent include conventionally known sulfur crosslinking agents such as powdered sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, sulfur chloride, thiuram-based vulcanization accelerators, and polymeric polysulfides.

[0036] Examples of the peroxide crosslinking agent include conventionally known peroxide crosslinking agents such as peroxyketals, dialkyl peroxides, peroxyesters, ketone peroxides, peroxydicarbonates, diacyl peroxides, and hydroperoxides.

[0037] Examples of the dechlorinating crosslinking agent include dithiocarbonate compounds, more specifically, quinoxaline-2,3-dithiocarbonate, 6-methylquinoxaline-2,3-dithiocarbonate, 6-isopropylquinoxaline-2,3-dithiocarbonate, 5,8-dimethylquinoxaline-2,3-dithiocarbonate, etc.

[0038] The amount of the crosslinking agent to be blended is preferably within a range of 0.1 to 2 parts by mass, more preferably within a range of 0.3 to 1.8 parts by mass, and even more preferably within a range of 0.5 to 1.5 parts by mass, per 100 parts by mass of the uncrosslinked rubber, from the viewpoint of preventing bleeding.

[0039] When a dechlorination crosslinking agent is used as a crosslinking agent, a dechlorination crosslinking accelerator may be used in combination. Examples of the dechlorination crosslinking accelerator include 1,8-diazabicyclo(5,4,0)undecene-7 (hereinafter abbreviated as DBU) or a weak acid salt thereof. The dechlorination crosslinking accelerator may be used in the form of DBU, but in terms of handling, it is preferable to use it in the form of a weak acid salt thereof. Examples of the weak acid salt of DBU include carbonate, stearate, 2-ethylhexyl acid salt, benzoate, salicylate, 3-hydroxy-2-naphthoate, phenol resin salt, 2-mercaptobenzothiazole salt, and 2-mercaptobenzimidazole salt.

[0040] The content of the dechlorination crosslinking accelerator is preferably within a range of 0.1 to 2 parts by mass, more preferably within a range of 0.3 to 1.8 parts by mass, and further preferably within a range of 0.5 to 1.5 parts by mass, based on 100 parts by mass of the uncrosslinked rubber, from the viewpoint of preventing bleeding.

[0041] A conductive agent can be blended into the elastic layer 14 to impart electrical conductivity. Examples of the conductive agent include electronic conductive agents and ionic conductive agents. Examples of the electronic conductive agent include carbon black, graphite, and conductive metal oxides. Examples of the conductive metal oxide include conductive titanium oxide, conductive zinc oxide, and conductive tin oxide. Examples of the ionic conductive agent include quaternary ammonium salts, borates, and surfactants. In addition, various additives may be appropriately added to the elastic layer 14 as necessary. Examples of the additives include lubricants, vulcanization accelerators, antiaging agents, light stabilizers, viscosity modifiers, processing aids, flame retardants, plasticizers, foaming agents, fillers, dispersants, defoamers, pigments, and mold release agents.

[0042] The elastic layer 14 can be adjusted to a desired volume resistivity by adjusting the type of crosslinked rubber, the amount of ionic conductive agent, the amount of electronic conductive agent, etc. 2 ~10 10 Ω cm, 10 3 ~10 9 Ω cm, 10 4 ~10 8 The range may be appropriately set to Ω·cm.

[0043] The thickness of the elastic layer 14 is not particularly limited, and may be appropriately set within a range of 0.1 to 10 mm depending on the application.

[0044] The surface layer 16 includes a binder polymer 16 a and roughness-imparting particles 18 .

[0045] The binder polymer 16a is a base polymer that constitutes the surface layer 16. Examples of the binder polymer 16a include urethane resin, polyamide resin, acrylic resin, acrylic silicone resin, butyral resin (PVB), alkyd resin, polyester resin, fluororubber, fluororesin, a mixture of fluororubber and fluororesin, silicone resin, silicone-grafted acrylic polymer, acrylic-grafted silicone polymer, nitrile rubber, and urethane rubber.

[0046] The binder polymer 16a is preferably one of polyurethane and polyamide. When the binder polymer 16a of the surface layer 16 is one of polyurethane and polyamide, the binder polymer 16a is made of a material with a high dielectric constant, and thus the chargeability of the roll surface is improved. In addition, the compression set is small, and the occurrence of streak images corresponding to the deformed portion when the charging roll 10 is set is suppressed. Polyurethane includes urethane resin, urethane rubber, and urethane elastomer. The polyamide may be modified. Examples of modified polyamide include alkoxylated polyamide such as N-methoxymethylated nylon.

[0047] The roughness-forming particles 18 are particles for imparting roughness to the surface of the surface layer 16. That is, the roughness-forming particles 18 are particles for imparting unevenness to the surface of the surface layer 16. As shown in FIG. 3, the roughness-forming particles 18 are disposed on the planar portion 24 and the groove portion 22 of the elastic layer 14. Due to the step between the planar portion 24 of the elastic layer 14 and the bottom surface 221 of the groove portion 22, the roughness-forming particles 18b on the planar portion 24 (roughness-forming particles 18b disposed on the planar portion 24) and the roughness-forming particles 18a on the groove portion 22 (roughness-forming particles 18a disposed on the groove portion 22) have different degrees of radial outward protrusion even though they have the same particle diameter. Due to the step between the planar portion 24 of the elastic layer 14 and the bottom surface 221 of the groove portion 22, the roughness-forming particles 18b on the planar portion 24 protrude radially outward more than the roughness-forming particles 18a on the groove portion 22.

[0048] The convex portion caused by the roughness forming particles 18b on the flat portion 24, which protrudes outward in the radial direction, becomes a portion that contacts the photoconductor, and the convex portion caused by the roughness forming particles 18a on the groove portion 22, which is located further inward in the radial direction, becomes a portion that does not contact the photoconductor. The convex portion caused by the roughness forming particles 18a on the groove portion 22 becomes a starting point of discharge. The surface layer 16 contains the roughness forming particles 18b on the flat portion 24, thereby ensuring an appropriate discharge space between the photoconductor and the charging roll 10. In addition, the surface layer 16 contains the roughness forming particles 18a on the groove portion 22, thereby ensuring a starting point of discharge. In this way, the surface unevenness of the surface layer 16 increases the discharge space between the photoconductor and the charging roll 10, promoting discharge. This improves charging properties and suppresses image defects such as horizontal streaks and unevenness. In the charging roll 10 according to the present invention, a step is provided between the flat portion 24 of the elastic layer 14 and the bottom surface 221 of the groove portion 22, so that even if the roughness-forming particles 18 contained in the surface layer 16 have the same particle diameter, an appropriate discharge space and a starting point for discharge can be easily formed between the photoconductor and the charging roll 10.

[0049] The surface roughness Rz of the surface layer 16 in the region M above the groove portion 22 is set to 2 μm or more and 16 μm or less. The surface roughness Rz of the entire surface layer 16 is set to 5 μm or more and 26 μm or less. This makes it possible to form an appropriate discharge space and a discharge starting point between the photoconductor and the charging roll 10.

[0050] If the surface roughness Rz of the surface layer 16 in the region M above the groove 22 is less than 2 μm, the surface roughness Rz is too small, the starting point of discharge is insufficient, and discharge is insufficient, so that black spots (fog) cannot be suppressed in the image after the durability test. From this viewpoint, the surface roughness Rz is more preferably 3 μm or more, and even more preferably 5 μm or more. On the other hand, if the surface roughness Rz of the surface layer 16 in the region M above the groove 22 exceeds 16 μm, the surface roughness Rz of the entire surface layer 16 becomes too large, making it difficult to discharge, and black spots (fog) cannot be suppressed in the image after the durability test. From this viewpoint, the surface roughness Rz is more preferably 15 μm or less, and even more preferably 12 μm or less.

[0051] If the surface roughness Rz of the entire surface layer 16 is less than 5 μm, the surface roughness Rz is too small, the starting point of discharge is insufficient, and discharge is insufficient, and black spots (fog) cannot be suppressed in the image after durability testing. From this viewpoint, the surface roughness Rz is more preferably 7 μm or more, and even more preferably 10 μm or more. On the other hand, if the surface roughness Rz of the entire surface layer 16 exceeds 26 μm, the surface roughness Rz becomes too large, making it difficult to discharge, and black spots (fog) cannot be suppressed in the image after durability testing. From this viewpoint, the surface roughness Rz is more preferably 25 μm or less, and even more preferably 20 μm or less.

[0052] The surface roughness Rz is a 10-point average roughness, which is the average value of values ​​measured at any five points in accordance with JIS B0601 (1994). The surface roughness Rz of the entire surface layer 16 can be measured by observation using a laser microscope (such as Keyence's "VK-9510"). In an image taken at 400x magnification, a value calculated in the surface roughness mode of an analysis program (program name: KEYENCE VK Analyzer analysis application) can be regarded as the surface roughness Rz of the entire surface layer 16. The surface roughness Rz of the surface layer 16 in the region above the groove portion 22 can be measured by observation using a laser microscope (such as Keyence's "VK-9510"). In the captured image, a value calculated in the surface roughness mode of an analysis program (program name: KEYENCE VK Analyzer analysis application) can be regarded as the surface roughness Rz of the entire surface layer 16. 2 The value calculated by selecting the above can be used as the surface roughness Rz of the surface layer 16 in the region above the groove portion 22.

[0053] The surface roughness Rz of the surface layer 16 can be adjusted by adjusting the groove width w of the groove portion 22, the groove depth d, the area ratio a / b of the bottom surface 221 of the groove portion 22 to the flat surface portion 24, the particle diameter of the roughness-forming particles 18, the thickness of the binder polymer 16a, etc.

[0054] As the roughness-forming particles 18, particles such as resin particles and inorganic particles that are used as the roughness-forming particles 18 added to the surface layer 16 of the charging roll are used. The material of the roughness-forming particles 18 is not particularly limited. The material of the roughness-forming particles 18 is preferably any one of polyurethane, polyamide, and acrylic resin. When the material of the roughness-forming particles 18 is any one of polyurethane, polyamide, and acrylic resin, the roughness-forming particles 18 are made of a material with a high dielectric constant, and thus the chargeability of the roll surface is improved.

[0055] The size of the roughness-forming particles 18 is not particularly limited, but from the viewpoint of forming appropriate unevenness and improving the uniformity of the discharge characteristics, the average particle diameter is preferably 3 μm or more and 32 μm or less. More preferably, the average particle diameter is 5 μm or more and 30 μm or less, and even more preferably, the average particle diameter is 10 μm or more and 30 μm or less. The average particle diameter of the roughness-forming particles 18 is expressed as the average of any 20 points when the surface of the surface layer 16 is observed with a laser microscope, and the diameter of the roughness-forming particles 18 visible during surface observation is taken as the particle diameter.

[0056] The roughness-forming particles 18 may be composed of one type of particles, or may be composed of two or more types of particles. First, one type of particles refers to particles of the same material. The same material may refer to particles made of polymers that are contained in polyurethane in a wide range, or particles that have the same monomer composition in a narrow range. More preferably, particles that have the same monomer composition in a narrow range may be considered to be the same. Second, one type of particles refers to particles with the same particle diameter. The same particle diameter refers to particles that have a uniform particle diameter. For example, the diameter of the roughness-forming particles 18 is measured at 50 arbitrary positions, the average is μ, the deviation is σ, and μ / σ is 4.97 or less. The diameter of the roughness-forming particles 18 can be measured by observing the diameter of the particles using a laser microscope (for example, Keyence's "VK-9510").

[0057] The roughness-forming particles 18 are preferably composed of one type of particle. If the roughness-forming particles 18 are composed of two or more types of particles with different materials or particle diameters, it becomes necessary to adjust the thickness of the binder polymer 16a covering the roughness-forming particles 18, taking into consideration the difference in the effect on the discharge characteristics due to the material and particle diameter of the roughness-forming particles 18. If the roughness-forming particles 18 are composed of one type of particle in terms of material and particle diameter, it is easy to adjust the thickness of the binder polymer 16a covering the roughness-forming particles 18. This can improve the uniformity of the discharge characteristics. In addition, if two types of particles with significantly different particle diameters are included, the particles of different sizes tend to aggregate and the dispersibility tends to decrease. If the roughness-forming particles 18 are composed of one type of particle in terms of particle diameter, it is easy to control the aggregation of the roughness-forming particles 18, so the uniformity of the surface roughness can be improved. Furthermore, when the roughness-forming particles 18 are composed of one type of particle in terms of particle diameter, the uneven shape of the elastic layer 14 is easily reflected in the surface unevenness of the charging roll, making it easy to control the surface unevenness of the charging roll.

[0058] In the surface layer 16, the binder polymer 16a has a predetermined thickness. The thickness t1 of the binder polymer 16a covering the roughness-forming particles 18 on the grooves 22 is set to be thicker than the thickness t2 of the binder polymer 16a covering the roughness-forming particles 18 on the flat surface 24. This makes it possible to adjust the amount of discharge on the roughness-forming particles 18 on the grooves 22 and the amount of discharge on the roughness-forming particles 18 on the flat surface 24 to be the same, thereby improving the uniformity of the discharge characteristics. This makes it possible to suppress the occurrence of black spot images. This is because the portion where the roughness-forming particles 18 exist on the flat portion 24 is grounded to the photoconductor and therefore has a lower discharge amount than the portion where the roughness-forming particles 18 exist on the groove portion 22. Therefore, in order to make the discharge amount the same at each position, it is necessary to make the film thickness of the portion where the roughness-forming particles 18 exist on the flat portion 24 thinner than the portion where the roughness-forming particles 18 exist on the groove portion 22, thereby increasing the electrostatic capacitance and increasing the amount of charge on the surface.

[0059] The difference (t1-t2) between the thickness t1 of the binder polymer 16a covering the roughness-forming particles 18 on the grooves 22 and the thickness t2 of the binder polymer 16a covering the roughness-forming particles 18 on the flat surface 24 is preferably 4 μm or more and 16 μm or less. When the thickness difference (t1-t2) is 4 μm or more, the amount of charge on the surface of the binder polymer 16a covering the roughness-forming particles 18 on the flat surface 24 becomes relatively large, and the environmental range in which black dot images do not occur is expanded. From this viewpoint, the thickness difference (t1-t2) is more preferably 5 μm or more, and even more preferably 6 μm or more. Furthermore, when the thickness difference (t1-t2) is 16 μm or less, the thickness is maintained at an appropriate level, so that appropriate unevenness is easily formed. This can improve the uniformity of the discharge characteristics. From this viewpoint, the thickness difference (t1-t2) is more preferably 15 μm or less, and even more preferably 12 μm or less.

[0060] The thickness t1 of the binder polymer 16a covering the roughness-forming particles 18 on the grooves 22 is preferably 5 μm or more and 20 μm or less. When the thickness t1 is 5 μm or more, the resistance of the discharge points tends to be uniform, and the discharge characteristics tend to be uniform. From this viewpoint, the thickness t1 is more preferably 6 μm or more, and even more preferably 7 μm or more. When the thickness t1 is 20 μm or less, an appropriate roughness is ensured on the surface of the surface layer 16 on the grooves 22, and a discharge area can be ensured. From this viewpoint, the thickness t1 is more preferably 18 μm or less, and even more preferably 15 μm or less.

[0061] The thickness t2 of the binder polymer 16a covering the roughness-forming particles 18 on the flat surface portion 24 is preferably 1.0 μm or more and 4.0 μm or less. When the thickness t2 is 1.0 μm or more, the resistance of the discharge portion is likely to be uniform, and the discharge characteristics are likely to be uniform. From this viewpoint, the thickness t2 is more preferably 1.5 μm or more, and even more preferably 2.0 μm or more. When the thickness t2 is 4.0 μm or less, an appropriate roughness is ensured on the surface of the surface layer 16, and a discharge area can be ensured. From this viewpoint, the thickness t2 is more preferably 3.5 μm or less, and even more preferably 3.0 μm or less.

[0062] The thicknesses t1 and t2 of the binder polymer 16a can be measured by observing the cross section using a laser microscope (such as Keyence's "VK-9510"). For example, the thickness of the binder polymer 16a is measured at five arbitrary positions of the binder polymer 16a covering the roughness-forming particles 18 on the groove portion 22, and t1 can be expressed by the average of the thicknesses. Also, the thickness of the binder polymer 16a is measured at five arbitrary positions of the binder polymer 16a covering the roughness-forming particles 18 on the flat portion 24, and t2 can be expressed by the average of the thicknesses.

[0063] In order to make the thickness t1 of the binder polymer 16a covering the roughness-forming particles 18 on the grooves 22 thicker than the thickness t2 of the binder polymer 16a covering the roughness-forming particles 18 on the flat surface portion 24, it is advisable to utilize both the instability of the surface energy of the roughness-forming particles 18 on the grooves 22 and the instability of the energy of the base rubber of the grooves 22. That is, it is advisable to utilize the fact that the roughness-forming particles 18 on the grooves 22 tend to gather and stabilize a large amount of the binder polymer 16a, and the fact that the base rubber of the grooves 22 tend to gather and stabilize a large amount of the binder polymer 16a.

[0064] The content of the roughness-forming particles 18 in the surface layer 16 is not particularly limited, but from the viewpoint of improving the dispersibility of the roughness-forming particles 18 and making it easier to ensure uniform electrostatic charge, the content is preferably 3 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the binder polymer 16a in the surface layer 16. More preferably, the content is 5 parts by mass or more and 30 parts by mass or less.

[0065] A conductive agent can be blended in the surface layer 16 to impart conductivity. Examples of the conductive agent include electronic conductive agents and ionic conductive agents. Examples of the electronic conductive agent include carbon black, graphite, and conductive metal oxides. Examples of the conductive metal oxide include conductive titanium oxide, conductive zinc oxide, and conductive tin oxide. Examples of the ionic conductive agent include quaternary ammonium salts, borates, and surfactants. In addition, various additives may be appropriately added to the surface layer 16 as necessary. Examples of the additives include plasticizers, leveling agents, fillers, vulcanization accelerators, processing aids, and mold release agents.

[0066] The volume resistivity of the surface layer 16 is preferably set to a semiconductive region from the viewpoint of electrostatic chargeability. 7 ~1.0×10 10 It is recommended to set it within the range of Ω·cm. Volume resistivity can be measured in accordance with JIS K6911.

[0067] The elastic layer 14 can be formed, for example, as follows: First, the shaft 12 is coaxially placed in the hollow portion of a roll molding die, and an uncrosslinked conductive rubber composition is injected and heated and cured (crosslinked), and then the composition is demolded, or the uncrosslinked conductive rubber composition is extruded onto the surface of the shaft 12 to form the elastic layer 14 on the outer periphery of the shaft 12.

[0068] Methods for forming the grooves 22 on the outer peripheral surface of the elastic layer 14 include grinding and molding. Either method can form the regular grooves 22 on the outer peripheral surface of the elastic layer 14. In the case of grinding, for example, a grindstone in contact with the outer peripheral surface of the elastic layer 14 is moved in one axial direction at a constant speed while a roll body having the elastic layer 14 is rotated at a constant speed around its axis, thereby forming the grooves 22 that regularly spiral along the axial direction on the outer peripheral surface of the elastic layer 14. In addition, for example, the grindstone is moved in one axial direction and then in the other axial direction, thereby forming a mesh-like groove 22 on the outer peripheral surface of the elastic layer 14, in which the grooves 22a that regularly spiral along the axial direction like a right-handed screw and the grooves 22b that regularly spiral along the axial direction like a left-handed screw intersect.

[0069] The surface layer 16 can be formed by using a material for forming the surface layer 16, applying the material to the outer peripheral surface of the elastic layer 14, and appropriately performing a drying process or the like. The material for forming the surface layer 16 may contain a dilution solvent. Examples of the dilution solvent include ketone-based solvents such as methyl ethyl ketone (MEK) and methyl isobutyl ketone, alcohol-based solvents such as isopropyl alcohol (IPA), methanol, and ethanol, hydrocarbon-based solvents such as hexane and toluene, acetic acid-based solvents such as ethyl acetate and butyl acetate, ether-based solvents such as diethyl ether and tetrahydrofuran, and water.

[0070] According to the charging roll 10 having the above configuration, the grooves 22 are formed on the outer peripheral surface of the elastic layer 14 in a regular spiral shape along the axial direction, and the groove width w / groove depth d of the grooves 22 and the area ratio a / b of the bottom surface 221 of the grooves 22 to the flat surface 24 are within a specific range, so that the roughness-forming particles 18 can be uniformly and well-balancedly arranged on both the flat surface 24 and the grooves 22 of the elastic layer 14, forming a desired surface roughness and forming a desired roughness difference between the flat surface 24 and the grooves 22 of the elastic layer 14, thereby adjusting the discharge amount to an appropriate level. Furthermore, the thickness of the binder polymer 16a covering the roughness-forming particles 18 on the grooves 22 is made thicker than the thickness of the binder polymer 16a covering the roughness-forming particles 18 on the flat surface 24, so that the discharge amount can be made uniform. This results in excellent uniformity in the discharge characteristics.

[0071] The charge roll 10 according to the present invention does not form surface irregularities on the charge roll by arranging two types of roughness-forming particles of different sizes, large and small, on the outer peripheral surface of the generally flat elastic layer, but forms a predetermined uneven shape on the outer peripheral surface of the elastic layer 14, and then arranges relatively uniform roughness-forming particles 18 of a predetermined size thereon to form surface irregularities on the charge roll 10. The roughness-forming particles 18 are arranged not only on the grooves 22 of the elastic layer 14 but also on the flat surface 24. As a result, the steps of the surface irregularities of the elastic layer 14 appear as the surface irregularities of the charge roll 10. If the roughness-forming particles 18 are relatively uniform, the surface irregularities of the elastic layer 14 are easily reflected on the surface of the charge roll 10. To arrange the roughness-forming particles 18 not only on the grooves 22 of the elastic layer 14 but also on the flat surface 24, the groove width w of the grooves 22 should not be too large or too small compared to the size of the roughness-forming particles 18. By having the groove width w of the groove portion 22 be a predetermined size, the roughness forming particles 18 can be arranged reliably and uniformly not only on the groove portion 22 but also on the flat portion 24. Similarly, the width of the flat portion 24 should not be too large or too small. In order to arrange the roughness forming particles 18 reliably and uniformly on the flat portion 24, a predetermined area ratio is preferable. In the present invention, a predetermined uneven shape is formed on the outer peripheral surface of the elastic layer 14, which makes it possible to increase the surface area of ​​the outer peripheral surface of the elastic layer compared to the outer peripheral surface of the elastic layer which is generally flat. This improves the ease of discharge. This is an effect that can be exerted even if, for example, the groove portion 22 of the elastic layer 14 is filled with the binder polymer 16a of the surface layer 16. This effect is a finding that has not been found before. From this point of view, the configuration of the present invention also has an advantage.

[0072] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the spirit of the present invention.

[0073] For example, in the above embodiment, the outer peripheral surface of the elastic layer 14 is formed with a mesh-like groove portion 22 in which groove portion 22a that regularly spirals in a right-handed manner along the axial direction and groove portion 22b that regularly spirals in a left-handed manner along the axial direction intersect, but the groove portion 22 formed on the outer peripheral surface of the elastic layer 14 may be either groove portion 22a that spirals in a right-handed manner or groove portion 22b that spirals in a left-handed manner. For example, as shown in FIG. 4, the groove portion 22 may have only groove portion 22b that spirals in a left-handed manner. The mesh-like groove portion 22 is more advantageous in terms of uniformity of roughness than either one of them. EXAMPLES

[0074] The present invention will be described in detail below using examples and comparative examples.

[0075] Example 1 <Preparation of Conductive Rubber Composition> A conductive rubber composition was prepared by compounding 100 parts by mass of isoprene rubber with 30 parts by mass of carbon black, 6 parts by mass of zinc oxide, 2 parts by mass of stearic acid, 1 part by mass of sulfur, 0.5 parts by mass of thiazole-based vulcanization accelerator, 0.5 parts by mass of thiuranium-based vulcanization accelerator, and 50 parts by mass of heavy calcium carbonate, and kneading the mixture for 10 minutes using an internal mixer adjusted to a temperature of 50°C.

[0076] As materials for the conductive rubber composition, the following materials were prepared. Isoprene rubber (IR): JSR "JSR IR2200" Carbon black: Cabot Japan "Show Black N762" Zinc oxide: Sakai Chemical Industry's "Zinc oxide type 2" Stearic acid: "Sakura Stearic Acid" made by Nippon Oil & Fats Sulfur: Powdered sulfur manufactured by Tsurumi Chemical Industry Co., Ltd. Thiazole-based vulcanization accelerator: "Noccela DM" manufactured by Ouchi Shinko Chemical Industry Co., Ltd. - Thiuram-based vulcanization accelerator: "Noccela TRA" manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Heavy calcium carbonate: Shiraishi Calcium's "Whiten B", average particle size 3.6μm

[0077] <Preparation of Elastic Layer> A core metal (diameter 8 mm) was set in a molding die (pipe-shaped), the above composition was poured, and the die was heated at 180°C for 30 minutes, cooled, and demolded to form an elastic layer made of a conductive rubber elastic body having a thickness of 1.9 mm on the outer periphery of the core metal. Next, while rotating a roll body having an elastic layer at a constant speed around its axis, a grindstone in contact with the outer periphery of the elastic layer was moved at a constant speed in one axial direction, and then the grindstone in contact with the outer periphery of the elastic layer was moved at a constant speed in the other axial direction, thereby forming a mesh-like groove portion in which groove portions regularly spiraling in a right-handed manner along the axial direction and groove portions regularly spiraling in a left-handed manner along the axial direction intersect on the outer periphery of the elastic layer, as shown in Figure 2. The conditions are as follows. Roll body rotation speed: 500 rpm Grindstone movement speed: 0.05m / s Wheel speed: 72m / s Grit size: #1500 Groove pitch: 0.3 mm

[0078] <Preparation of surface layer> The roughness-forming particles, binder polymer, and carbon black as a conductive agent were mixed to obtain the composition (parts by mass) shown in the table, and 200 parts by mass of methyl ethyl ketone (MEK) were added and mixed and stirred at a predetermined stirring speed to prepare a liquid composition for forming a surface layer. Next, while continuing to stir, this liquid composition was roll-coated on the outer peripheral surface of the elastic layer, and a heat treatment was performed to form a surface layer with a thickness of 1.0 μm on the outer periphery of the elastic layer. In this way, the charging roll of Example 1 was produced.

[0079] Example 2 <Preparation of Conductive Rubber Composition> A conductive rubber composition was prepared by compounding 100 parts by mass of NBR with 0.7 parts by mass of stearic acid, 5 parts by mass of zinc oxide, 2 parts by mass of hydrotalcite, 3 parts by mass of peroxide crosslinking agent, and 20 parts by mass of carbon, and stirring and mixing these with a stirrer.

[0080] As materials for the conductive rubber composition, the following materials were prepared. NBR: "Nipol 1041" made by Nippon Zeon Stearic acid: NOF Corporation's "Sakura Stearic Acid" Zinc oxide: Sakai Chemical Industry's "Zinc oxide type 2" Hydrotalcite: Kyowa Chemical Industry's "DHT4A" Peroxide crosslinking agent: NOF's "Percumil D40" Carbon: Ketjenblack International "Ketjenblack EC300J" <Preparation of Elastic Layer> The heating temperature was changed to 170° C., and an elastic layer made of a conductive rubber elastic body was molded in the same manner as in Example 1. Next, in the same manner as in Example 1, a mesh-like groove portion was formed in the outer peripheral surface of the elastic layer by polishing.

[0081] <Preparation of surface layer> A surface layer having a thickness of 1.0 μm was formed on the outer periphery of the elastic layer in the same manner as in Example 1. In this way, the charging roll of Example 2 was produced.

[0082] Example 3 <Preparation of Conductive Rubber Composition> To 100 parts by mass of hydrin rubber, 5 parts by mass of vulcanization aid, 10 parts by mass of carbon, 0.5 parts by mass of vulcanization accelerator, 2 parts by mass of sulfur, and 50 parts by mass of filler were added, and these were stirred and mixed with a stirrer to prepare a conductive rubber composition.

[0083] As materials for the conductive rubber composition, the following materials were prepared. Hydrin rubber (ECO, Zeon Corporation "Hydrin H1100") Vulcanization aid (zinc oxide, Mitsui Metals "Zinc Oxide Type 2") Carbon (Ketjenblack International "Ketjenblack EC300J") Vulcanization accelerator (2-mercaptobenzothiazole, "Noccela MP" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) Sulfur (Tsurumi Chemical Industry Co., Ltd., "Sulfax PTC") Filler (calcium carbonate, Shiraishi Kogyo's "Hakuenka CC") <Preparation of Elastic Layer> An elastic layer made of a conductive rubber elastic body was molded in the same manner as in Example 1. Next, in the same manner as in Example 1, a mesh-like groove was formed in the outer peripheral surface of the elastic layer by polishing.

[0084] <Preparation of surface layer> A surface layer having a thickness of 1.0 μm was formed on the outer periphery of the elastic layer in the same manner as in Example 1. In this way, the charging roll of Example 3 was produced.

[0085] (Examples 4, 5, 7, and 8) Charging rolls of Examples 4, 5, 7, and 8 were produced in the same manner as in Example 3, except that the surface layer material was changed.

[0086] Example 6 As shown in FIG. 4, a groove that regularly spirals like a left-handed screw was formed along the axial direction on the outer circumferential surface of the elastic layer, and the charging roll of Example 6 was produced in the same manner as in Example 3.

[0087] (Comparative Examples 1 to 8) Charging rolls of Comparative Examples 1 to 8 were produced in the same manner as in Example 3, except that the surface layer material was changed.

[0088] The materials used for the surface layers are as follows: Binder polymer (PA): Fine Resin FR-101 made by Lead City Binder polymer (PU): Negami Industrial Co., Ltd. "ART Resin UN-333" Roughness forming particles (PU <1> ): Negami Industrial Co., Ltd. "Art Pearl TK-100TR" average particle size 2μm Roughness forming particles (PU <2> ): Negami Chemical Industries "Art Pearl C-1000 transparent" average particle size 3μm Roughness forming particles (PU <3> ): Negami Chemical Industries "Art Pearl C-300 Transparent" average particle size 22μm Roughness forming particles (PU <4> ): Negami Chemical Industries "Art Pearl C-200 transparent graded product" average particle size 32μm Roughness forming particles (PU <5> ): Negami Chemical Industries "Art Pearl C-200 transparent graded product" average particle size 35μm Particles for roughness formation (PA): Toray "TR-2" average particle size 22μm Particles for roughening (PMMA): Negami Chemical Industries' "Art Pearl GR-200 transparent" average particle size 22μm Carbon black: Tokai Carbon "Seast 9H"

[0089] The surface and cross-sectional analysis of the polished elastic layer of the electrostatic roll were performed, and the groove width, groove depth, and area ratio a / b of the area a of the bottom surface of the groove to the area b of the flat surface were calculated. In addition, the surface roughness Rz and the thickness of the binder polymer of the surface layer were measured for the produced electrostatic roll.

[0090] (Uneven shape of elastic layer) The groove width of the groove was calculated from the average of the groove widths of 100 arbitrary grooves observed in an image of the outer peripheral surface of the elastic layer taken with a laser microscope. The groove depth of the groove was calculated from the average of the groove depths of 100 arbitrary grooves observed in an image of the radial cross section of the elastic layer taken with a laser microscope. The area ratio a / b of the area a of the bottom surface of the groove to the area b of the flat surface was calculated by taking an image of five arbitrary points of the outer peripheral surface of the elastic layer with a laser microscope, calculating the area a of the bottom surface of the groove and the area b of the flat surface observed in a specified range (0.1 mm × 0.1 mm) of the image, and averaging the ratios.

[0091] (Surface roughness Rz) The surface roughness Rz is the 10-point average roughness, which is the average value of values ​​measured at any five points in accordance with JIS B0601 (1994). The surface roughness Rz of the entire surface layer was measured by observation using a laser microscope (Keyence's "VK-9510"). In an image taken at 400x magnification, the value calculated in the surface roughness mode of an analysis program (program name: KEYENCE VK Analyzer analysis application) was taken as the surface roughness Rz of the entire surface layer. The surface roughness Rz of the surface layer in the area above the grooves was measured by observation using a laser microscope (Keyence's "VK-9510"). In the captured image, the value calculated in the surface roughness mode of an analysis program (program name: KEYENCE VK Analyzer analysis application) was taken as the surface roughness Rz of the entire surface layer. 2 The value calculated by selecting was taken as the surface roughness Rz of the groove portion.

[0092] (binder thickness) Measurements were made by observing the radial cross section of the surface layer at 400x magnification using a laser microscope (Keyence VK-X100). As shown in Figure 2, the thickness of the binder polymer covering the roughness-forming particles on the grooves (binder thickness t1) and the thickness of the binder polymer covering the roughness-forming particles on the flat surface (binder thickness t2) were measured. Each was measured at five randomly selected positions, and each was expressed as the average.

[0093] (Image rating: uneven) The produced charging roll was attached to the unit (black) of the actual machine (RICOH "MP C6004"), and images were printed at 25% density halftone in a 10℃ x 10% RH environment, and evaluation was performed after 500,000 sheets were printed. Images without unevenness were rated as good (◯), and images with unevenness were rated as poor (×).

[0094] (Image rating: horizontal streaks) The produced charging roll was attached to the unit (black) of an actual machine (RICOH "MP C6004"), and images were printed at 25% density halftone in a 10℃ x 10% RH environment, and an evaluation was performed after 500,000 sheets were printed. Images with no horizontal streaks were rated as particularly good (○), and images with horizontal streaks and a large impact on the image were rated as poor (×).

[0095] (Image rating: set streaks) The prepared charging roll was attached to the unit (black) of the actual machine (RICOH "MP C6004") and left for one week in a 50°C x 95% RH environment. After that, with the charging roll still attached to the unit (black) of the actual machine (RICOH "MP C6004"), an image was output at 25% density halftone in a 10°C x 10% RH environment. Images that had no set streaks were rated as particularly good (○), and images that had set streaks and were significantly affected by the image were rated as poor (×).

[0096] (Image evaluation: black spots (fog)) The produced charging roll was attached to the unit (black) of a real machine (RICOH "MP C6004"), and images were printed at 25% density halftone in a 10℃ x 10% RH environment, and an evaluation was performed after 500,000 sheets were printed. Images with no black spots were rated as good (○), and images with even one black spot were rated as bad (×).

[0097] [Table 1]

[0098] [Table 2]

[0099] In Comparative Example 1, the groove width is too small, so that the roughness-forming particles do not enter the grooves. Therefore, the difference between the surface roughness caused by the roughness-forming particles on the flat surface and the surface roughness caused by the roughness-forming particles on the grooves is small, and horizontal streaks occur due to insufficient charging. If roughness-forming particles of a size that fits into a small groove width are used, roughness that ensures sufficient discharge cannot be formed. In Comparative Example 2, the groove width is too large, so that the roughness-forming particles cannot be uniformly arranged in the grooves. Therefore, unevenness occurs after durability. If roughness-forming particles of a size that fits into a large groove width are used, the convex parts caused by the roughness-forming particles become too large, the surface roughness becomes too large, and the surface roughness cannot be made appropriate. As a result, uniform discharge characteristics cannot be obtained. In addition, in Comparative Example 2, the groove width is too large, so the binder polymer covering the roughness-forming particles on the grooves is likely to come into contact with the photoreceptor, resulting in wear not only of the binder polymer covering the roughness-forming particles on the flat surface and the roughness-forming particles underneath it, but also of the binder polymer covering the roughness-forming particles on the grooves and the roughness-forming particles underneath them, and as a result, the entire surface of the surface layer is worn away during durability testing, causing unevenness in the image.

[0100] In Comparative Example 3, the groove depth is too small, and the difference between the surface roughness caused by the roughness-forming particles on the flat surface and the surface roughness caused by the roughness-forming particles on the grooves is small, and horizontal streaks occur due to insufficient charging. If small roughness-forming particles are used in accordance with a small groove depth, roughness that ensures sufficient discharge cannot be formed. In Comparative Example 4, the groove depth is too large, and the roughness-forming particles placed in the grooves cannot form surface roughness on the grooves. For this reason, black spots (fog) occur in the image after durability testing. If large roughness-forming particles are used in accordance with a large groove depth, the difference between the surface roughness caused by the roughness-forming particles on the flat surface and the surface roughness caused by the roughness-forming particles on the grooves becomes too large, and discharge becomes difficult.

[0101] In Comparative Examples 5 and 6, the area ratio a / b between the area a of the bottom surface of the grooves and the area b of the flat surface is not within the specified range, and one of the ratios is too large. As a result, the uniformity of the surface irregularities is reduced, and uneven images are generated after durability testing.

[0102] In Comparative Example 7, the surface roughness Rz of the entire surface layer is too small, and the roughness is not sufficient to ensure sufficient discharge. As a result, horizontal stripes occur due to insufficient charging. In Comparative Example 8, the surface roughness Rz of the entire surface layer and the surface roughness Rz of the surface layer in the area above the grooves are too large, making it difficult to discharge. As a result, black spots (fog) occur in the image after durability testing.

[0103] On the other hand, in the examples, grooves are formed on the outer peripheral surface of the elastic layer in a regular spiral shape along the axial direction, and the groove width and depth of the grooves and the area ratio a / b of the bottom surface and flat surface of the grooves are within a specific range, the surface layer contains a binder polymer and roughness-forming particles, the roughness-forming particles are arranged on the flat surface and the grooves of the elastic layer, respectively, the surface roughness Rz of the surface layer in the region above the grooves and the surface roughness Rz of the entire surface layer are within a specific range, and the thickness of the binder polymer covering the roughness-forming particles on the grooves is thicker than the thickness of the binder polymer covering the roughness-forming particles on the flat surface. Therefore, in the examples, the problems of unevenness, horizontal streaks, and black spots (fog) after durability are suppressed in the image evaluation, and it can be seen that the uniformity of the discharge characteristics is excellent. In addition, no set streaks were generated in the image, and no peeling of the surface layer after durability was observed.

[0104] Although the embodiments and examples of the present invention have been described above, the present invention is not limited to the above-mentioned embodiments and examples, and various modifications are possible without departing from the spirit and scope of the present invention. [Explanation of symbols]

[0105] 10. Charging roll 12 Axial body 14 Elastic layer 16 Surface layer 18 Roughness forming particles 22 Groove 24 Plane part 16a Binder polymer 18a Grains for forming roughness on grooves 18b Particles for forming roughness on flat surface 221 Bottom surface of groove 22a A groove that spirals like a right-handed screw 22b Left-handed spiral groove w Groove width d Groove depth M Groove Area

Claims

1. The shaft body includes an elastic layer formed on an outer peripheral surface of the shaft body, and a surface layer formed on the outer peripheral surface of the elastic layer, A groove portion that draws a regular spiral shape along an axial direction is formed on an outer peripheral surface of the elastic layer, The groove width of the groove portion is 4 μm or more and 280 μm or less, The groove depth of the groove portion is 2 μm or more and 30 μm or less, an area ratio a / b of an area a of a bottom surface of the groove portion to an area b of a flat portion other than the groove portion in the outer peripheral surface of the elastic layer is 0.3 or more and 2.4 or less; the surface layer includes a binder polymer and roughness-imparting particles; the roughness-imparting particles are disposed on the planar portion and the groove portion of the elastic layer, a surface roughness Rz of the surface layer in the region above the groove portion is 2 μm or more and 16 μm or less; The surface roughness Rz of the entire surface layer is 5 μm or more and 26 μm or less, a thickness of the binder polymer covering the particles for forming roughness on the groove portion is greater than a thickness of the binder polymer covering the particles for forming roughness on the flat portion;

2. 2. The charging roll for an electrophotographic device according to claim 1, wherein the roughness-imparting particles are composed of one type of particles.

3. 3. The charging roll for an electrophotographic device according to claim 1, wherein the material of the roughness-forming particles is any one of polyurethane, polyamide, and acrylic resin.

4. 4. The charging roll for an electrophotographic device according to claim 1, wherein the average particle diameter of the roughness-imparting particles is 3 [mu]m or more and 32 [mu]m or less.

5. 5. The charging roll for an electrophotographic device according to claim 1, wherein a difference between a thickness of the binder polymer covering the roughness-forming particles on the flat portion and a thickness of the binder polymer covering the roughness-forming particles on the groove portion is 4 μm or more and 16 μm or less.

6. 6. The charging roll for an electrophotographic device according to claim 1, wherein the elastic layer contains at least one rubber selected from the group consisting of isoprene rubber, nitrile rubber, and hydrin rubber.

7. 7. The charging roll for an electrophotographic device according to claim 1, wherein the binder polymer of the surface layer is any one of polyurethane and polyamide.

8. 8. The charging roll for an electrophotographic device according to claim 1, wherein a mesh-like groove portion is formed on an outer peripheral surface of the elastic layer, in which groove portions that regularly form a right-handed spiral along the axial direction and groove portions that regularly form a left-handed spiral along the axial direction intersect with each other.

Citation Information

Patent Citations

  • Conductive member, manufacturing method thereof, process cartridge and image forming apparatus

    JP2007047322A

  • Electrifying roller and manufacturing method

    JP2007225995A

  • Conductive roll

    WO2018025870A1